2016
DOI: 10.1177/2374623816668275
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Scripts and the Sexual Behavior of Men and Women Who Use Pornography

Abstract: Using data collected from 1,880 heterosexual men and women residing in the United States, this study investigated the associations among gender, pornography consumption, and 20 sexual behaviors observed in popular pornography. Acts were grouped according to whether participants reported engaging or being interested in trying specific sexual behaviors as the (a) aggressor (e.g., hairpulling, spanking, or choking), (b) target (e.g., being spanked or choked), or (c) uncommon and/or degrading sexual activity (e.g.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 40 publications
(68 reference statements)
6
45
0
4
Order By: Relevance
“…Choking and other aggressive behaviors (such as hitting and forceful hair pulling) were also often described among the scary sexual experiences. Like anal sex, choking appears to have become more commonly portrayed in sexually explicit media and sexual choking behaviors (and interest in choking) are associated with pornography use (Bridges, Sun, Ezzell, & Johnson, 2016;Sun, Wright, & Steffen, 2017). In recent years, choking and various forms of breath restriction/ breath play have also become a part of nonsexual games that some adolescents engage in (Linkletter, Gordon, & Dooley, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Choking and other aggressive behaviors (such as hitting and forceful hair pulling) were also often described among the scary sexual experiences. Like anal sex, choking appears to have become more commonly portrayed in sexually explicit media and sexual choking behaviors (and interest in choking) are associated with pornography use (Bridges, Sun, Ezzell, & Johnson, 2016;Sun, Wright, & Steffen, 2017). In recent years, choking and various forms of breath restriction/ breath play have also become a part of nonsexual games that some adolescents engage in (Linkletter, Gordon, & Dooley, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Recent empirical studies support this assertion. Research has found particular support for sexual script theory as an explanation for the relationship between pornography use and certain sexual behaviors and attitudes, such as participation in casual sex (Braithwaite, Coulson, Keddington, & Fincham, 2015), “friends with benefits” (FWB) relationships (Braithwaite, Aaron, Dowdle, Spjut, & Fincham, 2015), gendered attitudes toward women (Wright & Bae, 2015), and sexual behaviors (Bridges, Sun, Ezzell, & Johnson, 2016; Sun, Bridges, Johnson, & Ezzell, 2016; Tomaszewska & Krahe, 2016, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As one example, although comparisons of viewers and nonviewers are common in pornography research (Bradley et al, 2016; Daneback et al, 2009; Emmers-Sommer, Hertlein, & Kennedy, 2013; Weaver et al, 2011), effect sizes may be enhanced if more nuance in viewing frequency is assessed. As another example, although reports of pornography viewing in the past 30 days or past year are common (Bradley et al, 2016; Braithwaite, Givens, Brown, & Fincham, 2015; Bridges et al, 2016; Carroll et al, 2008; Daneback et al, 2009; Poulsen, Busby, & Galovan, 2013), more chronologically encompassing consumption periods (e.g., from the onset of adolescence to the present—Stulhofer et al, 2012) may also increase variability in response and the magnitude of relations between variables. 7 As another example, consumption of specific genres of pornography could be measured.…”
Section: Discussionmentioning
confidence: 99%
“…Mahapatra and Saggurti (2014) controlled for sociodemographic (e.g., education, age) factors in their study of pornography use and extramarital sex but did not consider the potential confounding role of sexual attitudes. Bridges, Sun, Ezzell, and Johnson (2016) adjusted for gender, age, and religiosity in their study of pornography consumption and pornotypic behaviors (e.g., group sex, facial ejaculation) but did not include sexual attitudes as a covariate. Donevan and Mattebo (2017) compared engagement in sexual behaviors such as anal sex and one night stands across frequent, average, and infrequent pornography users but did not control for sexual attitudes.…”
Section: Confoundingmentioning
confidence: 99%